Penerapan Model Mind Mapping Pada Pembelajaran Transformasi Geometri - Domu, Ichdar; Wenas, Jhon; Warouw, Villya Febrina Fisca (Universitas Negeri Manado, 2020)
ABSTRACT. Â This research aims to examine the average of the student learning outcomes taught using the Mind Mapping model and those whom not using the Mind Mapping model which is the Problem Based Learning (PBL) model on geometry transformation lesson.Â This research was conducted at SMP Negeri 2 Tondano during odd semester of the 2019/2020 academic year. The subject in this research were students of grade IX-F as the experimental class and grade IX-G as the control class. Data collection in this research is done by giving test to the experimental dan control classes. The results showed that the average score of the students learning outcomes taught using the Mind Mapping model was 91.45 and the average of the students learning outcomes whom were not taught using the Mind Mapping model was 81.67. It means that the average of the students learning outcomes taught using the Mind Mapping model were more than the average of the students learning outcomes whom not using the Mind Mapping model which is Problem Based Learning (PBL) model on geometry transformation lesson.Â Key Words: Learning Outcomes, Mind Mapping